Effects of cultivar and fertilization on extensograph parameters of winter wheat flours - Boros, Norbert; B. Varga, Mária; Győri, Zoltán (Acta Agraria Debreceniensis, 2010)
In present paper we have examined the effect of mineral fertilization on the extensograph characteristics of wheat-flours. The baking quality of winter wheat is largely determined by cultivar, but it can be influenced by fertilization. Flours were from 4 cultivars grown at six nitrogen fertilizer. The average flour protein content of cultivars was very different (11.8, 13.0, 14.3, and 13.07%, respectively). We have found that the extensograph properties of dough are affected by mineral fertilization, nevertheless, different cultivars distinctly react to the increase of fertilizer doses. We estimates the correlation between flour protein content and extensograph properties, based on our investigations, it became obvious that the correlation between flour protein content and extensograph parameters is really strong.